Advanced Applications of Ionic Liquids - Akhter Siddique, Jamal; Akhter Siddique, Jamal; Ansari, Shahid Pervez; Khan, Aftab Aslam Parwaz (Elsevier Science, 2022)
Advanced Applications of Ionic Liquids discusses the intersection of nanotechnology with ionic liquids (ILs) and materials, along with opportunities for advanced engineering applications in various research fields. Novel materials at nano scales with ILs creates an upsurge in the thermal and electrochemical constancy of the nano scale particles, making them ideal for industrial applications. The implementation of ILs at nano scale includes an interaction of constituents, which is beneficial for electron transfer reactions. These new composites can be implemented as sensors, electronics, catalysts and photonics. Including ILs in polymer composites enhance electrochemical consistency, govern particle size, upsurge conductivity, reduce toxicity, and more. This book is a comprehensive reference for researchers working with IL based technologies for environmental and energy applications. - Covers all industrial aspects and advanced applications of ionic liquids (ILs) - Discusses the advanced applications of ILs across multiple fields, including industrial chemistry and chemical engineering - Includes a discussion of the use of ionic liquids in functional polymers, with applications for catalysis, energy conservation, sensors, and more